Replikasi Unidirectional pada Heterogen Database - Hendro Nindito; Evaristus Didik Madyatmadja; Albert Verasius Dian Sano (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The use of diverse database technology in enterprise today can not be avoided. Thus, technology is needed to generate information in real time. The purpose of this research is to discuss a database replication technology that can be applied in heterogeneous database environments. In this study we use Windows-basedMS SQL Server database to Linux-based Oracle database as the goal. The research method used is prototyping where development can be done quickly and testing of working models of the interaction process is done through repeated. From this research it is obtained that the database replication technolgy using Oracle Golden Gate can be applied in heterogeneous environments in real time as well.